Social Service Intervention Strategy in Encouraging the Transformation of Independence of Family Hope Program Recipients (PKH) in West Limboto District - Anatasia Putri Amuntu; Irwan Halid; Muh Firyal Akbar; Sri Lestari H. Gintulangi (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
The problem of poverty and the high dependence of Beneficiary Families (KPM) on the social assistance of the Family Hope Program (PKH) are still challenges in community empowerment efforts. Although PKH is designed to encourage independence, in practice there is still a gap between the program objectives and conditions in the field, especially in West Limboto District, so a more effective intervention strategy is needed from the Social Service. This study aims to analyze the intervention strategy of the Social Service in encouraging the transformation of the independence of PKH recipients and identify the supporting and inhibiting factors. The research method used is a qualitative approach with a descriptive type of research. The data collection technique is carried out through observation, interviews, and documentation, while data analysis uses data reduction, data presentation, and conclusion drawing with validity test through triangulation. The results of the study show that the intervention strategies carried out include aspects of Plan, Pattern, Position, Perspective, Ploy. However, the implementation is not optimal because there are still limited resources, lack of program integration, and low changes in the mindset of KPM. On the other hand, the support of social companions and empowerment programs are supporting factors in encouraging independence. The conclusion of this study emphasizes that the intervention strategy of the Social Service has not been fully effective in transforming the independence of KPM, so it is necessary to strengthen programs that are more integrated, sustainable, and based on community needs.